Historical notes on Heard and McDonald Islands - Roberts, Brian (Polar Record, 1950)
The discovery of Heard Island (lat. 53°; 10′ S., long. 73°; 35′ E.) has usually been attributed to Capt. John J. Heard of the American barque Oriental , who sighted the island on 25 November 1853 during a voyage from Boston to Melbourne. The relevant passage from Captain Heard's log book has been published by the American Geographical Society. He did not get nearer than twenty miles and mentions only one island, which can definitely be identified with Heard. Satisfactory evidence, however, has been found which shows that Heard Island was first sighted by the British sealer Peter Kemp, Master of the brig Magnet , on 27 November 1833. Kemp's discovery apparently remained unpublished, and his journal has been lost. The only surviving evidence of his voyage is a track chart preserved in the Hydrographic Department of the Admiralty.